The Module Validity of The Sub-Material Utilization of Medicinal Plant Biodiversity - Vinaloka, Widia; Syamswisna, Syamswisna; Tenriawaru, Andi Besse (Tarbiyah : Jurnal Ilmiah Kependidikan, 2022)
The aim of the study was to determine the feasibility of the module as a sub-material for the use of biodiversity for class X SMA. Using Research and Development (R&D) research methods with a qualitative descriptive approach. This study validated the instrument and validated the module teaching materials. The selection of validators with purposive sampling technique which consists of 5 validators. Module validation to obtain quantitative data accurately through a Likert scale. The assessment aspect of the module contains the feasibility of content, language, presentation, and graphics. The validation results obtained through the validator were analyzed using the CVR formula and continued to CVI, the results of the analysis of 4 aspects of the assessment namely the feasibility of content, language, presentation, and graphics consisting of 15 indicators of module feasibility assessment obtained a CVI value of 0.99 which is said to be a valid module and proper to use.The aim of the study was to determine the feasibility of the module as a sub-material for the use of biodiversity for class X SMA. Using Research and Development (R&D) research methods with a qualitative descriptive approach. This study validated the instrument and validated the module teaching materials. The selection of validators with purposive sampling technique which consists of 5 validators. Module validation to obtain quantitative data accurately through a Likert scale. The assessment aspect of the module contains the feasibility of content, language, presentation, and graphics. The validation results obtained through the validator were analyzed using the CVR formula and continued to CVI, the results of the analysis of 4 aspects of the assessment namely the feasibility of content, language, presentation, and graphics consisting of 15 indicators of module feasibility assessment obtained a CVI value of 0.99 which is said to be a valid module and proper to use.